2013
DOI: 10.1182/blood-2013-02-483750
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of imatinib cessation for CML patients with stable undetectable minimal residual disease: results from the TWISTER study

Abstract: Key Points• Approximately 40% of patients with undetectable minimal residual disease on imatinib can stop treatment without loss of molecular response.• Patients in treatment-free remission still have detectable BCR-ABL DNA several years after stopping imatinib.Most patients with chronic myeloid leukemia (CML) treated with imatinib will relapse if treatment is withdrawn. We conducted a prospective clinical trial of imatinib withdrawal in 40 chronic-phase CML patients who had sustained undetectable minimal resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
647
4
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 630 publications
(690 citation statements)
references
References 36 publications
24
647
4
15
Order By: Relevance
“…The majority of the relapses (58%) occurred in the first 6 months after imatinib interruption. The TWISTER study confirmed that stable treatment free remission at 24 months after imatinib interruption could be achieved in 47.1% of patients [18]. In both studies, all patients but 1 who relapsed, did not progress or develop BCR-ABL1 mutations and all of them remained sensitive to imatinib re-treatment.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The majority of the relapses (58%) occurred in the first 6 months after imatinib interruption. The TWISTER study confirmed that stable treatment free remission at 24 months after imatinib interruption could be achieved in 47.1% of patients [18]. In both studies, all patients but 1 who relapsed, did not progress or develop BCR-ABL1 mutations and all of them remained sensitive to imatinib re-treatment.…”
Section: Introductionmentioning
confidence: 71%
“…In the ISAV study 48% of patients relapsed, with an overall risk of relapse at 36 months of 52%. The fact that imatinib can be interrupted was already demonstrated in other trials such as the STIM and the TWISTER studies [16][17][18]22,23]. The relapse of approximately 50% of patients after 2 years of FUP is now a consistent figure across several studies, including patients treated with second generation TKIs [24].…”
Section: Discussionmentioning
confidence: 92%
“…Early studies were confined to patients with undetectable BCR-ABL1 transcripts by standard reverse transcriptase polymerase chain reaction (RT-PCR), and defined molecular recurrence as the reappearance of BCR-ABL1 transcript positivity 6,7 . More recent studies have specified recurrence as the loss of major molecular response (MMR, defined as BCR-ABL1/ABL1 transcript ratio of >0.1%, also called MR3 [molecular response of 3 logs below an arbitrary standard baseline]).…”
Section: Introductionmentioning
confidence: 99%
“…The definition of CMR as the complete absence of detectable BCR-ABL1 transcripts is limited by the sensitivity of the assay used for transcript measurement [24,25,27,28]. Thus, ELN recommends use of the term molecularly undetectable leukemia, together with the number of control gene transcripts, over the term CMR [11].…”
Section: Monitoring Molecular Responses To Tki Therapymentioning
confidence: 99%